AB0245 Anti-Cyclic Citrullinated Antibodies in Early Rheumatoid Arthritis-Correlation with Disease Activity and Musculoskeletal Ultrasonography. (9th June 2015) - Mitran, C.; Barbulescu, A.; Vreju, F.; Criveanu, C.; Ciurea, P.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease, associated with joint destruction, progressive disability and systemic complications. The discovery of autoantibodies recognising cyclic citrullinated peptides (anti-CCP) improved the early diagnosis of RA and the ability to identify patients with an increased risk of a more severe disease. An early assessment of inflammation and disease activity is essential for the therapeutic approach, establishing the evolution and prognosis. Objectives: To assess the presence and level of anti-CCP antibodies in a group of patients with early RA, and establish the correlations with disease activity and inflammatory changes determined using musculoskeletal ultrasonography. Methods: We enrolled 29 patients diagnosed with early RA, according to ACR-EULAR 2010 classification criteria, in Rheumatology Clinic, Emergency County Hospital Craiova, between September 2013-August 2014. usculoskeletal ultrasonography was performed using ESAOTE MyLab 25, by the same examiner. The presence of active synovitis was assessed both in grey scale and power-Doppler, according to OMERACT-EULAR consent Results: In our cohort with early RA patients, the mean age was 49.65±9.56 years, the mean value of ESR was 38.52±12.41mm/h and the mean CRP value 12.54±0.63 mg/dl; the mean value of anti-CCP antibodies was 141.2±218.2 U/ml. Regarding disease activity we found a mean value of 5.34±0.53 for DAS28(4v) and 9.54±4.81 for SDAI. Health assessment questionnaire established a mean value of 1.31±0.53 for HAQ. The ultrasound examination found active synovitis in all patients, with a mean number of joints with active synovitis of 5 (limits between 1 and 12). Evaluating the grade, we found grade 1 in all patients, 2 in 14 and grade 3 in 3 patients. Analysis of correlations between disease activity and anti-CCP antibodies found a positive, statistically significant correlation (r=0.44, p=0.001), as well as between anti-CCP antibodies and DAS28(4v) (r=0.453, p=0.001) and SDAI (r=0.472, p=0.009). Conclusions: Our findings showed that there was a significant association between the level of anti-CCP and severity of disease and inflammatory changes identified using musculoskeletal ultrasonography, fact that sustain their periodical assessment in patients with early rheumatoid arthritis. References: Mandl P, Naredo E, Wakefield RJ, Conaghan PG, D'Agostino MA. A systematic literature review analysis of ultrasound joint count and scoring systems to assess synovitis in rheumatoid arthritis according to the OMERACT filter.; OMERACT Ultrasound Task Force. J Rheumatol. 2011 Sep;38(9):2055-62. doi: 10.3899/jrheum.110424. Tian J, Chen J, Li F, Xie X, Du J, Mao N, Gao J. Grey scale and power Doppler ultrasonographic assessment of bone erosion and disease activity in early rheumatoid arthritis. J Cent South Univ (Med Sci)2013 Dec;38(12):1270-4. Karimifar M, Moussavi H, Babaei M, Akbari M.The association of immunoglobulin A, immunoglobulin G and anti-cyclic citrullinated peptide antibodies with disease activity in seronegative rheumatoid arthritis patients. J Res Med Sci. 2014 Sep;19(9):823-6. Acknowledgements: Dr. Carmen Mitran is a fellow of POSDRU grant no. 159/1.5/S/136893 grant with title: "Parteneriat strategic pentru creşterea calităţii cercetării ştiinţifice din universităţile medicale prin acordarea de burse doctorale şi postdoctorale – DocMed.Net_2.0" Disclosure of Interest: None declared